Interleukin 4 Gene–defective Mice Reconstituted with Wild-type Bone Marrow Fail to Produce Normal Immunoglobulin E Levels - Lange, Claudia (The Rockefeller University Press, 1998)
The ability to reconstitute interleukin (IL)-4(−/−) mice with bone marrow of IL-4(+/+) mice was investigated. The absence of the IL-4(−/−) gene in donor or recipient cells did not impair the reconstitution. All immunoglobulin (Ig) subsets occurred at normal serum levels except for IgE and to some extent IgG1. IgE production did not recover in the reconstituted mice over prolonged time. However, these mice were competent for IgE production, because a single intrasplenic injection of IL-4 restored IgE levels, which then remained constant. Wild-type mice reconstituted with wild-type bone marrow constantly had IgE serum levels comparable to untreated animals. In wild-type mice reconstituted with IL-4(−/−) bone marrow, IgE levels dropped gradually and disappeared by week 12. We make three unrelated but nonetheless important conclusions: (a) (immunoregulation) the tightly regulated IL-4 gene should be expressed constantly in low amounts (and with apparent absence of antigen stimulation) to keep the normal threshold of IgE; (b) (ontogeny of the immune system) an early unidentified source of IL-4 must be postulated which is lost in adult mice; and (c) (bone marrow transfer/gene therapy) under certain circumstances, the genotype of the recipient influences the reconstitution.